Forest owners as political actors. Issue 126 (December 2021) - Takala, Tuomo; Lehtinen, Ari; Hujala, Teppo; Tanskanen, Minna; Brockhaus, Maria; Tikkanen, Jukka; Toppinen, Anne
Abstract: Conflicting interests make forests an inevitably political issue. We examine the political roles that Finnish forest owners take as decision-makers and citizens. Inspired by post-political theories of democracy, we examine forest owners' aim of open, constructive treatment of the controversies between views, ideologies and actors. Our data consisted of a survey (n = 452) informed by an interview (n = 24). We applied a mixed-method critical discourse analysis. The forest owners produced four alternative discourses of forest-related controversies, the major controversy being that between productivism and environmentalism. The 'involved discourse' positioned itself in between these two ideologies, although closer to the former. From this position, it expressed an eagerness to discuss any issue with anyone. The 'pragmatist discourse' criticised ideological environmentalism but did not perceive its own productivist ideology. The 'receding discourse' perceived its own environmentalist ideology and criticised the productivist one but was not eager to discuss forest policy issues. The 'uninvolved discourse' excluded controversies, and thus the political dimension, from a forest owner's life. The involved discourse was closest to the constructed ideal of respectful, agonist, re-politicisation of forest issues. Recognition of one's own ideology while being comfortably close to the hegemonic view of the forest seemed to be the main factor behind this orientation. Yet, political views that challenged the status quo and demanded a transformative change towards sustainability were pushed into a silent antagonism. A major forest policy challenge is how to bring forest owners with these transformative ideas – the proponents of ecological citizenship – into the sphere of agonist re-politicisation. Highlights: Competing discourses affect how forest owners perceive their political roles. The roles reflected positions in the gradient from productivism to environmentalism. Environmental orientation led to silent antagonism from subordinate position. Blindness to the political dimension was common near the productivist core. Guidance towards active citizenship and agonist interaction is needed.